Kritik Objektifikasi Perempuan pada Lirik Lagu Nxde karya (G)-IDLE - Nabila Hamidah Ath Thahirah; Alex Sobur (Bandung Conference Series: Communication Management, 2024)
Abstract. The research entitled “Criticism of the Objectification of Women in the Song Lyrics Riffaterre's Semiotic (Analysis of the Lyrics of the Song Nxde by (G)-IDLE) was motivated by the public's interest in this song so that it went viral on various social media because the message contained social criticism, especially the objectification of women in the lyrics. Song lyrics can be used as a forum for sharing knowledge and views about social issues that affect a community or nation, as well as entertainment. This research aims to find out how the meaning is contained, especially regarding criticism of the objectification of women in the lyrics of the song Nxde through Riffaterre's semiotic theory approach in terms of four stages, namely, heuristics and hermeneutics, matrix, model and variant, and hypogram. The research method used is qualitative descriptive research. Data collection techniques in this research are observation and documentation. The research results show that heuristic and hermeneutic reading does not only mean criticism of objectification and stereotypes of women, but also how they rise up and accept themselves as they are. The matrix of the lyrics of this song is a stereotype of women and is objectified by other people. The model for the lyrics of this song is the character "I" who is a woman and the character "you". The hypogram of the lyrics of this song is for potential according to the matrix and for actual it is inspired by the story of Marilyn Monroe and Kurt Cobain's words Abstrak. Penelitian yang berjudul “Kritik Objektifikasi Perempuan pada Lirik Lagu (Analisis Semiotika Riffaterre pada Lirik Lagu Nxde karya (G)-IDLE)” ini dilatar belakangi oleh minatnya khalayak akan lagu ini sehingga viral di berbagai sosial media karena pesan yang mengandung kritik sosial terutama objektifikasi perempuan dalam liriknya. Lirik lagu dapat digunakan sebagai wadah untuk berbagi pengetahuan dan pandangan tentang masalah sosial yang mempengaruhi komunitas atau bangsa, selain sebagai hiburan. Penelitian ini bertujuan untuk mengetahui bagaimana makna yang terkandung terutama tentang kritik objektifikasi perempuann dalam lirik lagu Nxde melalui pendekatan teori semiotika Riffaterre ditinjau dari empat tahapan yaitu, heuristik dan hermeneutik, matriks, model dan varian, dan hipogram. Metode penelitian yang digunakan yaitu penelitian deskriptif kualitatif. Teknik pengumpulan data pada penelitian ini adalah observasi dan dokumentasi. Hasil penelitian menunjukkan pembacaan heuristic dan hermeneutic tidak hanya mengartikan kritik objektifikasi dan streotip Perempuan, namun bagaimana mereka bangkit dan menerima dirinya apa adanya. Matriks dari lirik lagu ini adalah streotip Perempuan dan dijadikan objektifikasi oleh orang lain. Model dari lirik lagu ini adalah tokoh “aku” yang merupakan wanita dan tokoh “kamu”. Hipogram dari lirik lagu ini adalah untuk potensial sesuai dengan matriks dan untuk actual terinspirasi dari kisah Marilyn Monroe dan Perkataan Kurt Cobain.